Regeneration dynamics and secondary metabolites in dendranthema grandiflorum (Ramat.) Kitam Through tissue culture (Bangladesh Journal of Botany, 2026)
Shoot tips and ray florets were utilized as explants for rapid mass propagation of Dendranthema grandiflorum.  In vitro shoot regeneration frequencies of 88 and 80 % were observed in shoot tips and ray florets, respectively, when cultured on MS medium supplemented with 1.0 mg/l BAP and 1.0 mg/l Kn, and BAP (1.0 mg/l) + NAA (0.5 mg/l). For rhizogenesis, microshoots transferred to half-strength MS medium supplemented with IBA; 0.2 mg/l) and IAA; 0.2 mg/l) achieved 80% root induction within 3-4 weeks. Comparative phytochemical profiling confirmed the presence of total phenols, tannins, and flavonoids in the one month old micropropagated clones. Quantifying the foundational phenolic and flavonoid pools prior to transplantation allows researchers to gauge whether the juvenile tissues possess a sufficient biochemical buffer to survive the acclimatization phase. Ex vitro hardening of well-developed plantlets yielded a 95% survival rate, followed by successful field acclimatization. Notably, the regenerated plants exhibited accelerated phenology, displaying earlier flowering compared to the donor mother plant.Bangladesh J. Bot. 55(2): 239-244, 2026 (June)